SISTEM PENILAIAN KINERJA SEBAGAI INTERVENSI TERHADAP PERSEPSI KEADILAN PADA OPERATOR MESIN CETAKPT TRISAKTI MUSTIKA GRAPHIKADIVISI SECURITY PRINTING - Pradana, Hendricus Ivan; Haryanti, Kristiana; Setyorini, Th. Dewi (PREDIKSI, 2012)
This study is conducted in order to compile performance appraisal for printing machine operators at PT Trisakti Mustika Graphika, Security Printing Division. This compilation is needed by the company because the older performance appraisal was deemed not to satisfy the operators sense of fairness many the operators felt being unfairly assessed under the older performance appraisal. Therefore, the objective of this research is to formulate a new performance appraisal based on Behavior Anchored Rating Scales (BARS) that can restore the operators fairness perception of performance appraisal.This research utilized one group pretest posttest experiment design. The performance appraisal system was created by the author based on the companys data. The result is From the study, it was found that the new performance appraisal did not significantly increase the operators fairness perception of performance appraisal. Although its effect on operators fairness perception is not significant, there were some signs that show the starting of the operators positive perception with the new performance appraisalSave to Mendeley